1992
DOI: 10.1111/j.1600-0404.1992.tb05064.x
|View full text |Cite
|
Sign up to set email alerts
|

CSF neurotransmitter metabolites and short-term outcome of patients in coma after head injury

Abstract: The main metabolites of the neurotransmitters noradrenaline, dopamine, and serotonin, methoxy-hydroxyphenylglycol (MHPG), homovanillic acid (HVA), and 5-hydroxyindoleacetic acid (5HIAA) respectively, were estimated by HPLC with electrochemical detection in CSF samples from 24 patients in coma after head injury, 1 to 12 (mean 3.0) days from accident, and from 24 age- and sex-matched subjects undergoing myelography for possible herniated disk. Analysis of variance with age as covariate, revealed significantly el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Cerebrospinal fluid sampling of catecholamine metabolites in persons with recent severe TBI indicates that levels of these neurotransmitters are elevated in the immediate post-injury period. 8,9 The duration of these elevations generally is brief, with normalization occurring during the acute recovery period. 8,9 The role of catecholaminergic dysfunction in the development of persistent post-traumatic cognitive impairment is not clearly established.…”
Section: Catecholaminesmentioning
confidence: 98%
See 1 more Smart Citation
“…Cerebrospinal fluid sampling of catecholamine metabolites in persons with recent severe TBI indicates that levels of these neurotransmitters are elevated in the immediate post-injury period. 8,9 The duration of these elevations generally is brief, with normalization occurring during the acute recovery period. 8,9 The role of catecholaminergic dysfunction in the development of persistent post-traumatic cognitive impairment is not clearly established.…”
Section: Catecholaminesmentioning
confidence: 98%
“…8,9 The duration of these elevations generally is brief, with normalization occurring during the acute recovery period. 8,9 The role of catecholaminergic dysfunction in the development of persistent post-traumatic cognitive impairment is not clearly established. Preliminary findings from studies pairing pharmacologic probes (i.e., dopaminergic agonists and alpha-2 adrenergic agonists) with functional magnetic resonance imaging in the laboratory of McAllister and colleagues suggest that catecholaminergic dysregulation plays a role in post-traumatic working memory impairments.…”
Section: Catecholaminesmentioning
confidence: 98%
“…6 Optimal levels enhance processing of contextually relevant cognitive, emotional, or behavioral information (signal) and inhibit processing of background information (noise). 8,9 The duration of these elevations generally is brief, with normalization occurring during the acute recovery period. The effects of catecholamines on cerebral information processing follow an inverted U-shaped dose-response curve.…”
Section: Catecholaminesmentioning
confidence: 99%
“…Increasing the signal-to-noise ratio in cerebral information processing systems generally is manifested clinically as an improvement in the speed and/or efficiency of cognition. 8,9 The role of catecholaminergic dysfunction in the development of persistent post-traumatic cognitive impairment is not clearly established. Accordingly, either deficient or excessive dopamine may interfere with such processing.…”
Section: Catecholaminesmentioning
confidence: 99%
“…Studies in patients in coma after severe head injury have shown increased concentrations of methoxyhydroxyphenylglycol (MHPG), 5-hydroxyindoleacetic acid (5HIAA), and homovanillic acid (HVA), the main metabolites of NA, 5HT, and DA, respectively [4,5,7,10]. In a previous publication [7], we reported increased concentrations of MHPG, 5HIAA, and HVA in CSF of a group of 24 patients in coma after severe head injury, compared with data from patients undergoing myelography for possible herniated disc. Higher 5HIAA concentrations were found in the patients who had a bad outcome compared to those with a good outcome.…”
Section: Introductionmentioning
confidence: 99%